'Common Sense Slimming' - How the contribution of Joan Robins, television's 'afternoon cook', was not the perfect-fit for the culture of the BBC in the 1950s. (September 2022) - Geddes, Kevin
Cooking on television after WWII mainly addressed 'the housewife' audience, while women themselves were presenting television cooking programmes. History has largely forgotten the presenter Joan Robins, who appeared alongside Philip Harben and Marguerite Patten on BBC broadcasts of the late 1940s and 1950s. Robins specialised in 'common-sense' cookery, nutrition, and health, including a controversial slimming programme that featured advice that was later disputed by the British Medical Association. Robins' ideas and innovations were not always welcomed by the BBC, who preferred more straightforward cookery demonstrations, resulting in her turning her back on broadcasting to concentrate on her other careers.